PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT RAJAERBA INDOCHEM - Fernando; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The purpose to determine the effect of compensation and work environment on employee performance PT. Rajaerba Indochem. This research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires to 35 respondents, all of whom were employees of Rajaerba Indochem. The research method using partially and simultaneous linear regression analysis. The results of the study indicate that simultaneous or partially, compensation and work environment have a positive and significant effect on employee performance PT. Rajaerba Indochem